Intertextual Ecologies through Mapping the Spiritual Dialogue of Nature in Rumi and Emerson: A Systematic Literature Review - Juliastuti, Juliastuti; Zamrud, Mardliyah Pratiwi; Thayyib, Magfirah (Journal of Language and Literature Studies, 2026)
This article investigates the eco-spiritual poetics of nature by tracing the intertextual resonance between Jalāl al-Dīn Rumi’s Sufi mysticism and Ralph Waldo Emerson’s transcendentalism, demonstrating that both traditions conceptualize nature not as a passive backdrop but as a sacred medium through which divine consciousness is continuously disclosed. The thematic analysis reveals three interrelated findings that collectively clarify the study’s contribution. First, the EcoPoetics and Nature cluster shows that elemental imagery earth, water, wind, and sky functions as a shared poetic grammar through which spiritual meaning is ecologically encoded, echoing broader ecopoetic arguments that language itself mediates human nature relationships (e.g., Knickerbocker’s ecopoetics of sensory engagement and Marland’s ecological literary frameworks). Second, the Spiritual Resonance cluster demonstrates that silence, love, and voice operate as ecological metaphors across both traditions, suggesting that inner spiritual transformation and environmental awareness are mutually reinforcing processes rather than separate ethical domains; this finding aligns with influential ecocritical critiques that reposition affect, ethics, and spirituality at the center of environmental humanities discourse (Cohen; James). Third, the Intercultural Dialogue cluster provides the most conceptually significant insight: by mapping convergences between tawḥīd (divine unity) and transcendental unity, the study evidences a transcultural eco spiritual cosmology that unsettles rigid East West binaries and reframes comparative literature as a site of ethical planetary dialogue. Methodologically, the study’s adoption of a PRISMA-guided Systematic Literature Review marks a substantive advancement for literary and comparative studies. By synthesizing 34 rigorously selected studies from an initial corpus of 312 records, the research demonstrates that SLR-based literary synthesis can move ecocriticism beyond impressionistic comparison toward a replicable, evidence-driven analytical model. The findings collectively imply that literature functions as a mediating bridge between sacred ecology and contemporary environmental ethics, offering humanities scholarships a structured pathway to engage global ecological crises without sacrificing interpretive depth. In this sense, the study not only contributes substantively to Rumi–Emerson scholarship but also establishes a transferable methodological template for 21st-century comparative ecocriticism, particularly in spiritually inflected literary traditions.